Checking the underlying structure of R-SPQ-2F using covariance structure analysis / Comprobación de la estructura subyacente del R-SPQ-2F mediante análisis de estructura de covarianza. Issue 1 (2nd January 2018) - López-Aguado, Mercedes; Gutiérrez-Provecho, Lourdes
Abstract: The R-SPQ-2F is an instrument used in many studies to measure learning approaches. However, its internal structure is still a matter of debate. It is important to confirm its underlying structure in order to find out which variables are being measured with it. A survey method is used with 279 students of the Faculty of Education at the University of León, and alternative models found in the literature are compared using covariance structure analysis, specifically, Confirmatory Factor Analysis (CFA). We conclude that the structure that best fits the data is a two-factor structure in line with the results obtained in other studies. Future research should take these two primary factors into account when interpreting their findings. Solutions are also offered for improving the scale with the original 20 items.